2007
DOI: 10.1039/b516347c
|View full text |Cite
|
Sign up to set email alerts
|

Bisintercalator natural products with potential therapeutic applications: isolation, structure determination, synthetic and biological studies

Abstract: Echinomycin is the prototypical bisintercalator, a molecule that binds to DNA by inserting two planar chromophores between the base-pairs of duplex DNA, placing its cyclic depsipeptide backbone in the minor groove. As such, it has been the focus of an extensive number of investigations into its biological activity, nucleic acid binding and, to some extent, its structure-activity relationships. However, echinomycin is also the parent member of an extended family of natural products that interact with DNA by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 130 publications
3
72
0
2
Order By: Relevance
“…Reflecting these distinct affinities, quinomycin antibiotics show different inhibitory activities against various enzymes, such as DNA polymerase, RNA polymerase, reverse transcriptase and topoisomerase. 5 Although thiocoraline has promising antitumor activity, most members of this family of compounds are toxic to mammalian cells. 5 To improve the profiles between antitumor activity and toxicity, we studied the biosynthetic pathway of 1 and synthesizing its derivatives by genetic engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting these distinct affinities, quinomycin antibiotics show different inhibitory activities against various enzymes, such as DNA polymerase, RNA polymerase, reverse transcriptase and topoisomerase. 5 Although thiocoraline has promising antitumor activity, most members of this family of compounds are toxic to mammalian cells. 5 To improve the profiles between antitumor activity and toxicity, we studied the biosynthetic pathway of 1 and synthesizing its derivatives by genetic engineering.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although thiocoraline has promising antitumor activity, most members of this family of compounds are toxic to mammalian cells. 5 To improve the profiles between antitumor activity and toxicity, we studied the biosynthetic pathway of 1 and synthesizing its derivatives by genetic engineering. Recently, we have achieved de novo production of 1 using E. coli as a heterologous host.…”
Section: Introductionmentioning
confidence: 99%
“…The first target was des-N-tetramethyl triostin A (2b) or TANDEM, which bis-intercalates into DNA and exhibits a distinct preference for AT sequences in contrast to echinomycin displaying a different DNA preference for GC-rich sequences. 4 In order to produce 2b in E. coli, we hypothesize the need to 1) inactivate the two methylation (M) domains of the 340-kDa bimodular NRPS Ecm7, responsible for the N-methylation of the cysteine and the valine residues in the core peptide backbone, and 2) omitting Ecm18, responsible for forming the thioacetal-bridge. 5 To this end, we had to redesign the echinomycin biosynthetic pathway into a TAN-DEM biosynthetic pathway.…”
Section: Synthesis Of Echinomycin Derivatives By Inactivation Of Specmentioning
confidence: 99%
“…4 This class of antibiotics are dimeric cyclic peptides with a pair of chromophores and have potent DNA binding affinities at a level between nM to M with different sequence selectivities. Reflecting these distinct affinities, bis-intercalator antibiotics such as 1-4 show fairly different inhibitory activities against various enzymes such as DNA polymerase, RNA polymerase, reverse transcriptase and topoisomerase.…”
Section: Enzymatic Synthesis Of Echinomycin and Its Derivativesmentioning
confidence: 99%
“…[27] Several studies of synthetic variants have shown that the composition of the depsipeptide linker has a profound effect on the sequence selectivity of the bisintercalators. [34] A family of nine cysteine (Cys)-containing quinoline tripeptides (Fig. 4b) was oxidized to form a library of 45 unique disulfide dimers.…”
Section: Reaction Conditions and Analysismentioning
confidence: 99%